Omega-limit sets and robust stability for switched systems with distinct equilibria⁎Research supported in part by AFOSR grant FA9550-18-1-0246 and NSF grant ECCS-1508757. Issue 2 (2020) - Baradaran, Matina; Teel, Andrew R.
Abstract: This work characterizes the asymptotic behavior that results from switching among asymptotically stable systems with distinct equilibria when the switching frequency satisfies an average dwell-time constraint with a small average rate. The asymptotic characterization is in terms of the Ω-limit set of an associated ideal hybrid system containing an average dwell-time automaton with the rate parameter set equal to zero. This set is globally asymptotically stable for the ideal system. The actual switched system, including small disturbances, constitutes a small perturbation of this ideal system, resulting in semi-global, practical asymptotic stability.